2010
DOI: 10.2147/opth.s9546
|View full text |Cite
|
Sign up to set email alerts
|

Intracameral vancomycin following cataract surgery: An eleven-year study

Abstract: AimTo compare the incidences of endophthalmitis after cataract operations before and after introduction of intracameral vancomycin at the end of surgery.MethodsA retrospective analysis was performed of presumed infectious endophthalmitis after cataract surgery from January 1, 1998 to December 31, 2008. From January 2001, the practice of using intracameral vancomycin at the end of cataract surgery was introduced. The period before introduction of intracameral vancomycin is considered as period A and that after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 25 publications
1
31
0
Order By: Relevance
“…An intracameral injection of antibiotics, including cefuroxime, vancomycin, and moxifloxacin, has been shown to be well tolerated and effective at reducing the rate of postoperative endophthalmitis [1113,14 ▪▪ ,15 ▪▪ ,16 ▪ ,17 ▪ ]. In the case of vancomycin, a retrospective analysis of more than 16 000 cases showed that an intracameral injection of 1-mg vancomycin reduced the rate of postoperative endophthalmitis more than 37-fold [12]. Studies have also shown that an intracameral injection of vancomycin or moxifloxacin is well tolerated for the cornea and retina [18,19 ▪ ,20 ▪ ].…”
Section: Introductionmentioning
confidence: 99%
“…An intracameral injection of antibiotics, including cefuroxime, vancomycin, and moxifloxacin, has been shown to be well tolerated and effective at reducing the rate of postoperative endophthalmitis [1113,14 ▪▪ ,15 ▪▪ ,16 ▪ ,17 ▪ ]. In the case of vancomycin, a retrospective analysis of more than 16 000 cases showed that an intracameral injection of 1-mg vancomycin reduced the rate of postoperative endophthalmitis more than 37-fold [12]. Studies have also shown that an intracameral injection of vancomycin or moxifloxacin is well tolerated for the cornea and retina [18,19 ▪ ,20 ▪ ].…”
Section: Introductionmentioning
confidence: 99%
“…In order to reduce the risk of postoperative endophthalmitis, antibiotics have been used in irrigating fluid perioperatively43 44 or injecting intracamerally45 during cataract surgery. In the Centers for Disease Control and Prevention (CDC) guidelines for appropriate use of vancomycin46 and the report by the Rockefeller University Workshop47 published in 1994, the prophylactic use of vancomycin was discouraged in view of the risk of increasing the prevalence of VRE and MRSA.…”
Section: Discussionmentioning
confidence: 99%
“…8,61,62 Anijeet et al in a 11 year retrospective study of more than 16000 patients found that intracameral vancomycin (1mg in 0.1ml) reduced the incidence of endophthalmitis from 0.3% to 0.008%. 63 Vancomycin is very effective against gram positive bacteria including methicillin resistant staphylococcus aureus (MRSA) but is ineffective against gram negative bacteria. 8 There are concerns regarding intracameral vancomycin causing cystoid macular oedema and its limited microbial spectrum, that preclude its widespread use.…”
Section: Issn 0972-0200mentioning
confidence: 99%